The Impact of the Teaching at the Right Level Approach on Critical Reasoning in Mathematics Learning in Elementary Schools - Diniyarti, Ni Wayan; Agustika, Gusti Ngurah Sastra (Universitas Pendidikan Ganesha, 2023)
Education in schools currently has problems, especially in terms of adjusting students' ability levels. A unified approach that needs to be applied to this condition is the Teaching at the Right Level approach. So teaching at the right level means teaching given to students according to their level of ability. This research aims to analyze the influence of the Teaching at the Right Level approach on critical reasoning abilities in mathematics lessons for fourth grade elementary school students. This type of research uses quasi-experimental research. This research design is a non-equivalent control group design. The population of this study was 180 students. The sample in this research consisted of 71 students. The sample selection in this study used a cluster random sampling technique. Data on students' critical reasoning abilities in mathematics lessons was collected using an essay test method which was then analyzed using the t-test. The results of data analysis obtained tcount= 9.87, while at a significance level of 5% and dk 69 it was obtained ttable= 1.995 so that tcount= 9.87 was greater than ttable= 1.995, so Ho was rejected and Ha was accepted, which means there were differences in the groups of students being studied. Through the Teaching at the Right Level Approach with groups of students who are not taught using the Teaching at the Right Level Approach in fourth grade elementary school students.